SOCIALIZATION ON THE LEGALITY OF ESTABLISHING AN ENGLISH LANGUAGE COURSE INSTITUTION IN MATA AIR TARUS VILLAGE - Alexander Wewo, Jeremia (LPPM Univ. Ibn Khaldun Bogor, 2025)
This community service was motivated by the absence of an English language course institution in Mata Air Tarus Village. As a non-formal educational institution, a course institution plays an important role in improving the competence and skills of the community, especially in the field of English as an international language. However, the establishment of a course institution must comply with applicable regulations. This community service aims to provide an understanding to the Village Head and Village Officials of Mata Air Tarus, as well as the founders of the language course institution, regarding the legal aspects of establishing such an institution. The methods used in this community service include surveys, presentations, and discussions or question-and-answer sessions. The results of the community service and discussions revealed that the establishment of a course institution must comply with the Ministry of Education and Culture Regulation Number 81 of 2013 on the Establishment of Non-Formal Education Units to avoid conflicting with existing laws and regulations. The recommendations provided are the need for a unified understanding among the Village Head, Village Officials, Course Institution Founders, and the Education Office to ensure the implementation of Non-Formal Education that can improve the quality of the community.